2017
DOI: 10.3389/fpls.2017.00401
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study for Pre-harvest Sprouting Resistance in a Large Germplasm Collection of Chinese Wheat Landraces

Abstract: Pre-harvest sprouting (PHS) is mainly caused by the breaking of seed dormancy in high rainfall regions, which leads to huge economic losses in wheat. In this study, we evaluated 717 Chinese wheat landraces for PHS resistance and carried out genome-wide association studies (GWAS) using to 9,740 DArT-seq and 178,803 SNP markers. Landraces were grown across six environments in China and germination testing of harvest-ripe grain was used to calculate the germination rate (GR) for each accession at each site. GR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 82 publications
3
58
0
Order By: Relevance
“…In addition, a novel QTL for GC was also identified on chromosome 1B. Zhou et al [37] identified three main QTLs for PHS resistance by GWAS, including a novel locus on chromosome 5D and two loci co-located with Tamyb10-1 genes on chromosomes 3A and 3D. Furthermore, 32 GC-related QTLs (GCR-QTL) were also detected, and a strong correlation was observed between the number of GCR-QTL and seed germination rate.…”
Section: Grain Colormentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a novel QTL for GC was also identified on chromosome 1B. Zhou et al [37] identified three main QTLs for PHS resistance by GWAS, including a novel locus on chromosome 5D and two loci co-located with Tamyb10-1 genes on chromosomes 3A and 3D. Furthermore, 32 GC-related QTLs (GCR-QTL) were also detected, and a strong correlation was observed between the number of GCR-QTL and seed germination rate.…”
Section: Grain Colormentioning
confidence: 99%
“…The interaction between QTL epistasis (Q × Q) and the environment (Q × E, Q × Q × E) for PHS resistance has been studied to understand the complex genetic structure of QTL [213][214][215]. In wheat, PHS resistance is controlled jointly by multiple QTLs located an almost 21 chromosomes (1A, 1B, 2A, 2B, 2D, 3A, 3B, 3D, 4A, 4B, 5B, 5D, 6A, 6B, 6D, 7A, 7B and 7D) [1,14,18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][216][217][218][219][220] (Table 1).…”
Section: Qtl/genes Identified For Phs Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…A total of 189 wheat landraces from ten major wheat-growing zones (Table S2) [40], as well as 583 wheat prebreeding lines/varieties covering most important wheat-producing regions in China (Table S3), were also included in the current study.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Quantitative trait loci (QTL) for PHS and dormancy have been identified throughout the allohexaploid wheat genome (Zanetti et al 2000;Ogbonnaya et al 2008;Munkvold et al 2009;Kulwal et al 2012;Jaiswal et al 2012;Zhou et al 2017;Martinez et al 2018). While homologues of ABA signaling genes have been found on wheat chromosomes 3A, 4A, and 5A, only Viviparous-1/ABA-insensitive3 (VP1/ABI3) has been linked to differences in wheat PHS tolerance (Nakamura and Toyama 2001;McKibbin et al 2002;Nakamura et al 2007).…”
Section: Introductionmentioning
confidence: 99%